Stepping on the cracks - Hahn, Mary Downing (New York : Clarion Books, 1991)
In 1944, while her brother is overseas fighting in World War II, eleven-year-old Margaret gets a new view of the school bully Gordy when she finds him hiding his own brother, an army deserter, and decides to help him.
1 12 13 16 17 18 19 20 21 34 35 38
Keywords: World War, 1939-1945 -- United States -- Fiction; Bullies -- Fiction